MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR MATERI PRANATA DAN PENYIMPANGAN SOSIAL MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBANTUAN MEDIA GAMBAR PADA SISWA KELAS VIII SMPN 4 PARINGIN KABUPATEN BALANGAN TAHUN PELAJARAN 2013/2014 - Febtika Reysne (Universitas Lambung Mangkurat, 2014)
Class Action Research is conducted at class VIII SMPN 4 Paringin. They are 29 research subjects (twenty-nine) who study from May to June 2014. This study aims to increase student activity and learning outcomes through the use of learning model CIRC (Cooperative Integrated Reading and Composition) aided drawing. Where this type of research is classroom action research (PTK) which uses a model by Kemmis spiral round and Taggart consisting of four stages: planning, implementation, observation, and reflection. In this study, teachers do five stages in applying the CIRC learning model that survey, question, read, Recite, reviews. Results of research in cycle 1 mean aspects of the overall student after learning implemented using model-assisted drawing on material CIRC social institutions including low category with mastery learning only reached 55.17%. In cycle 2 all aspects of student activity on average achieve active category with learning completeness reached 86.21%. While the response of the students showed a positive result, students are helped and pleased with CIRC assisted learning model image.Keywords: CIRC learning model, student activity, and Learning Outcomes